ANALISIS MASALAH PEMBELAJARAN PADA OPERASI HITUNG BILANGANBULAT DI MASA PANDEMI COVID-19 - Sutama; Fitri Handayani; Yulia Maftuhah Hidayati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes a study about the learning problems of integer counting operations during the COVID-19 pandemic era. The study was qualitative descriptive research with case study methods. The study involved the students of class VI di SDN 1 Jambukidul Ceper Klaten. Techniques of data collection were carried out by applying the observation, interviews, and documentation. The validity of data used was a triangulation of sources, methods, and theories. Data were also analyzed through Milles & Huberman analysis techniques. The results showed that the learning problems of integer counting operationsduring the COVID-19 pandemic were (1) the abstract material characteristics that made students difficult to digest the meaning of problems into mathematical language; (2) limited space for teachers to control student learning attitudes, and (3) students’ low motivation andlearning outcomes about integer counting operations. In this relation, the researcher recommended that further studies are needed to be studied related to the selection of innovative learning models and media that are considered effective for the integer counting operating material, especially in the COVID-19 pandemic era.